Targeted Sequencing of 242 Clinically Important Genes in the Russian Population From the Ivanovo Region - Ramensky, Vasily E.; Ershova, Alexandra I.; Zaicenoka, Marija; Kiseleva, Anna V.; Zharikova, Anastasia A.; Vyatkin, Yuri V.; Sotnikova, Evgeniia A.; Efimova, Irina A.; Divashuk, Mikhail G.; Kurilova, Olga V.; Skirko, Olga P.; Muromtseva, Galina A.; et al. (Frontiers in Genetics, 2021)
We performed targeted sequencing of 242 clinically important genes mostly associated with cardiovascular diseases in a representative population sample of 1,658 individuals from the Ivanovo region northeast of Moscow. Approximately 11% of 11,876 detected variants were not found in the dbSNP or reported earlier in the Russian population. Most novel variants were singletons and doubletons in our sample, and virtually no novel alleles presumably specific for the Russian population were able to reach the frequencies above 0.1-0.2%. The overwhelming majority (99.3%) of variants detected in this study in three or more copies were shared with other populations. We found two dominant and seven recessive known pathogenic variants with allele frequencies significantly increased compared to those in the gnomAD non-Finnish Europeans. Of the 242 targeted genes, 28 were in the list of 59 genes for which ACMG recommended reporting of incidental findings. Based on the number of variants detected in the sequenced subset of ACMG59 genes, we approximated the prevalence of known pathogenic and novel or rare protein-truncating variants in the complete set of ACMG59 genes in the Ivanovo population at 1.4% and 2.8%, respectively. We analyzed the available clinical data and observed the incomplete penetrance of known pathogenic variants in the 28 ACMG59 genes: only one individual out of 12 with such variants had the phenotype most likely related to the variant. When known pathogenic and novel or rare protein-truncating variants were considered together, the overall rate of confirmed phenotypes was about 19%, with maximum in the subset of novel protein-truncating variants. We report three novel protein truncating variants in APOB and one in MYH7 observed in individuals with hypobetalipoproteinemia and hypertrophic cardiomyopathy, respectively. Our results provide a valuable reference for clinical interpretation of gene sequencing in Russian and other populations.